Efektivitas Media Pembelajaran Interaktif Berbasis Multimedia untuk Meningkatkan Kemampuan Literasi Sains Siswa SMA - Dorojatin, Siti Aisyah; Akhdinirwanto, Raden Wakhid (UNIB Press, 2026)
physics plays a significant role in the advencement of science and technology; however, physics learning in schools is often perceived as challenging, and students’ scientific literacy skills are still considered insufficient. This study aimed to evaluate the effectiveness of interactive multimedia-based learning media in improving senior high scholl students’ scientific literacy in physics. The research employed a quantitative approach using a pre-experimental design with a one-group pretest-posttest model. The research subjects consisted of 36 eleventh-grade students (Class XI-1) at a senior high scholl in Kebumen Regency. Data were collected using a scientific literacy test comprising five indicators: observing, measuring, predicting, concluding, and communicating. Data analysis was conducted through quantitative descriptive analysis using percentage scores and N-Gain analysis. The results showed that students’ initial scientific literacy levels varied, with percentages of 73.72%, 72.14%, 62.94%, 63.78%, and 75.08%. After the implementation of interactive multimedia-based learning media, post-test scores increased to 85.89%, 83.39%, 76.22%, 77.92%, and 89.53%. The N-Gain values ranged from 0.36 to 0.58, which fall into the moderate category. These findings indicate that interactive multimedia-based learning media are effective in enhancing students’ scientific literacy skills.